A Critical Review of Digital Marketing: Effect of Flow and Impulse Buying - Rahmawati Azizah Mt; Ria Octavia (Jurnal Economia, 2021)
Abstract: This study aims to examine the influence of user belief on flow, willingness to buy on flow, and flow on impulse buying behavior. The subjects of this research include Students/College Students, Civil Servants, Private Employees, Lecturers/Teachers, Professionals (accountants, consultants, etc.). The technique used is non-probability sampling , purposive sampling, with a total sample of 300 respondents aged 17 to 45 and are users of the digital application, Shopee, in Indonesia. The research instrument was an online questionnaire and was analyzed using multiple linear regression analysis. The results of this study showed that the dimension of the perceived usefulness of user belief has a positive effect on flow. Willingness to buy has a positive effect on flow and flow has a positive effect on impulse buying. Meanwhile, the ease of use dimension of the user belief variable has no positive effect on flow.Keywords: flow, willingness to buy, user belief, impulse buying behavior. Tinjauan Kritis Pemasaran Digital: Pengaruh Flow dan Pembelian Impulsif Abstrak: Penilitian ini bertujuan untuk menguji pengaruh kepercayaan pengguna (user belief) terhadap flow, willingness to buy terhadap flow, dan flow terhadap perilaku pembelian spontan. Subjek penelitian ini meliputi Pelajar/Mahasiswa, PNS, Karyawan Swasta, Dosen/Guru, Profesional (akuntan, konsultan, dll). Teknik yang digunakan adalah non-probability sampling dengan jenis purposive sampling dengan kriteria usia 17 hingga 45 tahun dengan total sampel 300 responden dan merupakan pengguna aplikasi digital Shopee di Indonesia. Instrumen penelitian ini adalah kuesioner yang dibuat secara daring dan dianalisis dengan menggunakan analisis regresi linier berganda. Hasil penelitian ini menemukan bahwa dimensi manfaat yang dirasakan dari kepercayaan pengguna berpengaruh positif terhadap flow, willingness to buy berpengaruh positif terhadap flow dan  flow berpengaruh positif terhadap pembelian spontan. Sedangkan, dimensi kemudahan menggunakan dari variabel kepercayaan pengguna tidak berpengaruh positif terhadap flow.Kata kunci: flow, willingness to buy, kepercayaan pengguna, perilaku pembelian spontan.